The association between childhood hunger experiences and health in middle and old age: a longitudinal study over 10 years - Dongxu Li; Xi Guo; Weile Zhang; Wenhui Li; Tianjiao Zhang; Zelin Liu; Min Su; Zhengrong Li (BMC Public Health)
Abstract Background A significant relationship is present between childhood hunger experiences (CHEs) and health, but explorations of the longitudinal persistence of this relationship and its mediating mechanisms are still lacking. This study aims to evaluate the effects of CHEs on health in middle and old age and determine the underlying mechanisms. Methods Using data from the five 2011—2020 China Health and Retirement Longitudinal Study (CHARLS) and the 2014 China Life History Survey Questionnaire, a sample of 9,909 individuals aged 45 years and older who participated in all six surveys was obtained. We conducted panel analyses, used Probit and ordinary least squares regression models to analyze the effects of CHEs on the health in middle and old age, and used stepwise regression tests to analyze the mediators of the relationship. Results CHEs significantly predicted self-assessment of health (β = −0.18; 95% CI: −0.23, −0.12), the probability of receiving medical treatment (β = −0.09; 95% CI: −0.13, −0.05), depression (β = −0.30; 95% CI: −0.35, −0.25), memory (β = −0.13; 95% CI: −0.18, −0.07), and cognitive function (β = −0.13; 95% CI: −0.26, −0.00). The effects of CHEs showed an aggravating trend regarding depression and cognitive function, and a mitigating trend regarding self-assessed health and memory. Smoking, exercising, and sleep duration were revealed as transmitting factors of the effects of CHEs on health. Conclusion CHEs had a negative impact on the health of middle and old age. While their effects on depression and cognitive function gradually worsen, the effects on self-assessed health and memory were mitigated over time. Lifestyle factors such as smoking, exercising, and sleep duration were transmitting factors of the health effects of CHEs. Thus, the health status of individuals who experience childhood hunger warrants attention.